STRATEGIC ADVANTAGES AND DISADVANTAGES FOR RURAL TOURISM DEVELOPMENT IN DINARIC ALPS/CASE TROPOLJE - Đorđević-Milošević, Suzana; Dražić, Gordana Dragutin; Milovanović, Jelena; Đorđević, Slađana (Economics of Agriculture, 2021)
The improvement of life quality in rural areas is an overall goal of all development strategies in the Western Balkans countries. Rural tourism represents the quality option for diversification of income and employment opportunities in Tropolje region (Canton 10 in Bosnia and Herzegovina). Therefore, the goal of this study is to identify strategic advantages and disadvantages for tourism development in Tropolje region of Dinaric Alps and provide guidelines for its development. The SWOT analysis combined with AHP method was used. In seven domains, 29 strengths, 31 weakness, 25 opportunities and 24 threats were determined, with total intensity 154, 202, 140 and 144 and average rating of influence intensity 5.3, 6.5, 5.6, 5.8, respectively. A significant advantage for tourism development were linked to short supply chains based on natural and cultural heritage of the region.